Parallel Computational Fluid Dynamics 1999 2000
DOI: 10.1016/b978-044482851-4/50015-3
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Implementation of the Discontinuous Galerkin Method

Abstract: This paper describes a parallel implementation of the discontinuous Galerkin method. The discontinuous Galerkin is a spatially compact method that retains its accuracy and robustness on non-smooth unstructured grids and is well suited for time dependent simulations. Several parallelization approaches are studied and evaluated. The most natural and symmetric of the approaches has been implemented in an object-oriented code used to simulate aeroacoustic scattering. The parallel implementation is MPI-based and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
14
1
Order By: Relevance
“…The super linear speed up in Fig. 3 can be attributed to the cache effect [6]. Speed up from the parallelization of the overall algorithm versus different number of processors will be presented in the conference.…”
Section: Mpi Parallelization Of the Modelmentioning
confidence: 97%
“…The super linear speed up in Fig. 3 can be attributed to the cache effect [6]. Speed up from the parallelization of the overall algorithm versus different number of processors will be presented in the conference.…”
Section: Mpi Parallelization Of the Modelmentioning
confidence: 97%
“…We have allowed the computation of auxiliary diagnostic variables between the call of send and receive. Further code revision could include the computation of the right-hand side and internal flux computations as described in Baggag et al (1999). In Algorithm 3 we describe how we overlap the computation of auxiliary variables and the computation of the gradient of the solution for the diffusion operator with the communication of the fluxes.…”
Section: Overlapping For the Dg Methodsmentioning
confidence: 99%
“…This allows the computation of internal edge and element integra communication. We have allowed the computation of auxiliary diagnostic variables between th Further code revision could include the computation of the right hand side and internal flux co (Baggag et al (1999)). In Algorithm 3 we describe how we overlap the computation of auxiliary va 8 Most notable about the implementation explained above is that, even in the absence of additional computation to be completed during communication, the packing and unpacking of the buffers provides some data movement to be accomplished while waiting for messages to be received.…”
Section: Overlapping For the Dg Methodsmentioning
confidence: 99%
“…Moreover, for large simulation in 3D, the use of supercomputers and scalable parallel algorithms is indispensable. Early research on the parallel implementation of DG for various applications can be found in [2,8,43,7].…”
Section: Introductionmentioning
confidence: 99%